2015
DOI: 10.1039/c5cc07226c
|View full text |Cite
|
Sign up to set email alerts
|

N and S co-doped porous carbon spheres prepared using l-cysteine as a dual functional agent for high-performance lithium–sulfur batteries

Abstract: Nitrogen and sulfur co-doped porous carbon spheres (NS-PCSs) were prepared using L-cysteine to control the structure and functionalization during the hydrothermal reaction of glucose and the subsequent activation process. As the sulfur hosts in Li-S batteries, NS-PCSs combine strong physical confinement and surface chemical interaction to improve the affinity of polysulfides to the carbon matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 31 publications
1
72
0
Order By: Relevance
“…Therefore, it is believed that heterogeneous doping of carbon material can improve the electrochemical performance of Li-S batteries through enhanced interaction between polar functional group and polysulde. [29][30][31] However, further progress is still imperative on the design and synthesis of novel carbon materials with regard to the following aspects: (i) homogeneous distribution of heteroatoms, ideally in situ doping from precursor during synthesis; (ii) a thin, exible and very conductive mesoporous structure used for sulfur host with easily accessible pores for lithium ions and provided a facile electron pathway; (iii) an easily manageable template that can be processed at mild conditions.…”
Section: -9mentioning
confidence: 99%
“…Therefore, it is believed that heterogeneous doping of carbon material can improve the electrochemical performance of Li-S batteries through enhanced interaction between polar functional group and polysulde. [29][30][31] However, further progress is still imperative on the design and synthesis of novel carbon materials with regard to the following aspects: (i) homogeneous distribution of heteroatoms, ideally in situ doping from precursor during synthesis; (ii) a thin, exible and very conductive mesoporous structure used for sulfur host with easily accessible pores for lithium ions and provided a facile electron pathway; (iii) an easily manageable template that can be processed at mild conditions.…”
Section: -9mentioning
confidence: 99%
“…The oxygen-containing groups on NS-G (288.8 and 290.5 eV), such as COOH and C-OH, can interact with T-Nb 2 O 5 by chemical bonds, acting as effective anchoring sites to bridge T-Nb 2 O 5 and NS-G. As shown in Fig. 4c, the N 1s spectrum can be fitted into three particular peaks with binding energy at 396.1, 398, 400.2 and 402.9 eV, which correspond to the nitride N, pyridinic N, pyrrolic N and graphitic N, respectively [38]. It was reported that the existence of pyridinic N and pyrrolic N can contribute to the synergistic effect of NS-G and T-Nb 2 O 5 , thus improving the electrochemical activity of the hybrid [39].…”
Section: Results and Descussionmentioning
confidence: 99%
“…To overcome above hurdles, various carbon materials including porous carbon particles,, carbon nanotubes,, carbon nanofibers and graphene, as the sulfur host have been widely exploited, due to their high surface area and excellent electronic conductivity. However, because of weak physical limitation of carbon materials on sulfur, the dissolution of polysulfide and the instability of long cycle remain unsolved ,.…”
Section: Introductionmentioning
confidence: 99%